Various Types of Potential Drug Plants in Muhammad Sabki Urban Forest Jambi City - Nursanti, Nursanti; Novriyanti, Novriyanti; Wulan, Cory (Media Konservasi, 2018)
The urban forest of Muhammad Sabki is one of city green open space that have many functions and potential to developed, especially plants that can be used as medicine. Medicinal plant is one of non timber forest product which is not only used by communities around the forest but also by urban communities. However, data on potentially herbal medicinal species in this urban forest have not been found. The recent research limited to the diversity of vegetation and wildlife. This research conducted for 4 months on 2017 in the area of Muhammad Sabki’s Urban Forest. A total of 50 sampling units are sized 2 m x 2 m and 5 m x 5 m, created randomly on this area consider of forest homogeneity. Based on the inventory, its found as many as 149 species of plants that have potential as a medicine. However, the analysis result obtained 50% of the total species are plants that used as medicine by the communities around world. The dominant types of plants that useful as medicine in this region are members of Rubiaceae family, 9 types (6%). The parts of plant organs that commonly used are leaves, as much as 36%. Keywords: medicinal plant, plant utilization, urban forest